Strontium–Alix interaction enhances exosomal miRNA selectively loading in synovial MSCs for temporomandibular joint osteoarthritis treatment - Wenxiu Yuan; Jiaqi Liu; Zhenzhen Zhang; Chengxinyue Ye; Xueman Zhou; Yating Yi; Yange Wu; Yijun Li; Qinlanhui Zhang; Xin Xiong; Hengyi Xiao; Jin Liu; et al. (International Journal of Oral Science)
Abstract The ambiguity of etiology makes temporomandibular joint osteoarthritis (TMJOA) “difficult-to-treat”. Emerging evidence underscores the therapeutic promise of exosomes in osteoarthritis management. Nonetheless, challenges such as low yields and insignificant efficacy of current exosome therapies necessitate significant advances. Addressing lower strontium (Sr) levels in arthritic synovial microenvironment, we studied the effect of Sr element on exosomes and miRNA selectively loading in synovial mesenchymal stem cells (SMSCs). Here, we developed an optimized system that boosts the yield of SMSC-derived exosomes (SMSC-EXOs) and improves their miRNA profiles with an elevated proportion of beneficial miRNAs, while reducing harmful ones by pretreating SMSCs with Sr. Compared to untreated SMSC-EXOs, Sr-pretreated SMSC-derived exosomes (Sr-SMSC-EXOs) demonstrated superior therapeutic efficacy by mitigating chondrocyte ferroptosis and reducing osteoclast-mediated joint pain in TMJOA. Our results illustrate Alix’s crucial role in Sr-triggered miRNA loading, identifying miR-143-3p as a key anti-TMJOA exosomal component. Interestingly, this system is specifically oriented towards synovium-derived stem cells. The insight into trace element-driven, site-specific miRNA selectively loading in SMSC-EXOs proposes a promising therapeutic enhancement strategy for TMJOA.